Idiotypes on major histocompatibility complex-restricted virus-immune cytotoxic T lymphocytes (The Rockefeller University Press, 1981)
Specificity-associated determinants could be demonstrated on major histocompatibility complex (MHC)-restricted virus-immune cytotoxic T lymphocytes (CTL) using antisera raised in syngeneic mice. This result indicates that the number of clonotypes sufficiently small to allow the detection of such idiotypic determinants. The functional properties of three anti-idiotypic antisera were tested in blocking studies and by idiotypic antisera plus complement. Whereas the former test did not reveal any results obtained from binding studies, i.e., all three anti- idiotypic antisera specifically reacted with CTL of the type used for immunization and had no effect on syngeneic influenza-immune CTL, syngeneic alloreactive CTL, or NDV-immune CTL of an H-2-disparate strain. These results are discussed in terms of current models for MHC- restricted CTL responses.